Effect of assistive reading software on high school students with learning disabilities: A pilot study. - Chiang, Hsin-Yu (Ariel); Liu, Chien-Hsiou; Lee; Shih, Yi-Nuo (Work, 2012)
Objective: This research project was designed to test the immediate effect of using assistive reading software - Kurzweil 3000 (K-3000) for high school students with learning disabilities (LD) to improve their English reading and other school performances. Participants: 29 Taiwanese high school students with LD were randomly assigned to one of two groups: (1) use of the K-3000 or (2) control group (using a pen and paper) Methods: Both groups were asked to complete the standardized measurements using pen and paper a pre-test. Students in experiment group used the K-3000 to do the post-test after they were familiarized with the K-3000, while the students in the control group used pen and paper for the post-test. The differences between the pre-test and post-test of two groups were analyzed. Results: The results suggested that the K-3000 had an immediate impact on students' English word recognition and pronunciation. However, the use of K-3000 did not have a significant influence on the students' general English proficiency, learning adjustment, and academic self-perception. Conclusions: The use of K-3000 had a positive effect on students' English word recognition. The reason why there was no significant change in students' other performances could be due to the length of the intervention.